Analysis of Blood Flow Velocity and Pressure Signals using the Multipulse Method - Derek H. Justice; H. Joel Trussell; Mette S. Olufsen (Mathematical Biosciences and Engineering)
This paper shows how the multipulse methodfrom digital signal processing can be used to accurately synthesizesignals obtained from blood pressure and blood flow velocity sensors duringposture change from sitting to standing. Themultipulse method can be used to analyze signals that are composed ofpulses of varying amplitudes. One of the advantages of the multipulsemethod is that it is able toproduce an accurate and efficient representation of the signalsat high resolution.The signals are represented as a set of input impulses passed throughan autoregressive (AR) filter. The parameters that define the AR filtercan be used to distinguish different conditions.In addition, the AR coefficients can betransformed to tube radii associated with digital wave guides, as wellas pole-zero representation. Analysis of the dynamics of themodel parameters have potential to provide better insight and understandingof the underlying physiological control mechanisms. For example, our dataindicate that the tube radii may be related to the diameter of theblood vessels.